2016
DOI: 10.21608/jappmu.2016.48270
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Feeding Some Forage Shrubs on Milk, Blood Parameters of Ewes and Growth Performance of Their Offsprings in Northern Coast.

Abstract: Forty mature Barki ewes at late pregnancy , 3-4 years old and 45.2±0.47 kg live body weight (LBW) divided into equal four groups were used in this work. This experiment aimed to evaluate the effect of feeding Acacia (AC) Acacia saligna , Atriplex (AT) Atriplex halimus, Cassava (CA) Manihot esculenta. compared to berseem (Trifolium Alexandrinum) hay (BH) on yield, chemical composition and rheological properties of milk, hematological and biochemical blood parameters of ewes, and growth performance of their offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
4
6
0
Order By: Relevance
“…Fig ( ), it's worth noting that total gain and average daily gain of lambs (males and females) was not affected at different ages affected by their mothers feeding shrubs plants. These results agreement with Shetaewi et al (2001), Fasae et al(2015) and El-Saadany et al (2016). This means that feeding ewes during pre-and postpartum period on different forage types in this study was save without adversely effects on growth performance of lambs produced.…”
Section: Performance Of Offspring'ssupporting
confidence: 92%
See 1 more Smart Citation
“…Fig ( ), it's worth noting that total gain and average daily gain of lambs (males and females) was not affected at different ages affected by their mothers feeding shrubs plants. These results agreement with Shetaewi et al (2001), Fasae et al(2015) and El-Saadany et al (2016). This means that feeding ewes during pre-and postpartum period on different forage types in this study was save without adversely effects on growth performance of lambs produced.…”
Section: Performance Of Offspring'ssupporting
confidence: 92%
“…In agreement with the present results, Abdalla et al, (2013) found that fat percentage in goat milk was not affected by type of roughages. Also, El-Saadany et al, (2016) cleared that there was a non-significant tendency of decrease in fat content in ewes milk fed Cassava as compared to other groups during all lactation weeks.…”
Section: Results Inmentioning
confidence: 84%
“…The concurrent results come in agreement with those obtained by Shetaewi et al (2001); Fasae et al (2015) and EL-Saadany et al (2016) who recorded differences (P<0.05) between ewes fed Acacia, Atriplex and Cassava when compared with those fed Berseem hay in total gain and average daily gain of lambs. On the other hand, these results are not in accordance with those obtained by Mohammady et al (2014) who reported higher weaning weight and daily gain (P<0.05) in Barki lambs fed BH when compared with those fed tanniniferous plants shrubs.…”
Section: Average Weekly Milk Productionsupporting
confidence: 92%
“…Plasma globulin while increased in ewes fed BH it decreased in those fed tanniniferous plants. EL-Saadany et al (2016) found significant increase in total plasma protein concentration between experimental groups (Acacia, Atriplex and Cassava vs. Hay). With regard to albumin, Shaker et al (2008) recorded that plasma albumin was higher in Barki lambs fed mixture of Acacia and Atriplex.…”
Section: B Protein Fractionsmentioning
confidence: 74%
See 1 more Smart Citation